Financial development and growth: where do we stand? - Levine, Ross (Estudios de Economía, 2016)
In spite of the recent theoretical and empirical work that suggests that financial systems exert a first-order, causal impact on economic growth, economists are still not very able of providing policy makers with detailed blueprints of how to create growth-promoting financial systems. The profession has only recently assembled broad cross-country data on financial structure and taken initial steps on comparing bank-based and market-based systems. This paper selectively reviews evidence on banks, markets, and financial structure. In terms of banks, the paper discusses why banks emerge, what they do, and how they affect economic performance. Next, it discusses evidence on the legal, accounting, and regulatory determinants of healthy banking development. The evidence suggests that legal and regulatory reforms that strengthen creditor rights, contract enforcement, and accounting practices boost banking sector development and accelerate economic growth. The paper next examines the impact of stock markets on economic growth. Finally, the debate on financial structure is reviewed. Is a bank-based or a market-based financial system better for promoting economic development? New research finds that establishing a legal environment that rigorously protects the rights of investors is fundamentally more important than any considerations involving comparisons between bank-based or market-based systems. Both banks and markets provide complementary services to the economy with positive implications for economic performance.